2012
DOI: 10.3724/sp.j.1227.2012.00292
|View full text |Cite
|
Sign up to set email alerts
|

The effect of water spreading system on the functionality of rangeland ecosystems

Abstract: In recent decades, the control of floods is an efficient management practice for the rehabilitation of rangelands in most arid and semiarid areas. To evaluate the benefits, we used the Landscape Function Analysis (LFA) method to assess the function of patches and qualitative capability of a rangeland ecosystem in Gareh Bygone region, Fars province, southwestern Iran. Landscape functionality depends on soil, water and nutrient (collectively called "resources") conservation and use within a given ecosystem. Many… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…Our results are in agreement with the higher levels of infiltration and nutrient cycling indexes found in shrub patches in semiarid degraded steppes of Spain (Maestre and Cortina, 2004). These results can be explained by the role of shrub patches in maintaining soil stability (Bidgoli et al, 2012) and improved infiltration due to root development as found in rangeland ecosystems of Iran (Forouzeh and Sharafatmandrad, 2012).…”
Section: Landscape Function Recovery Of Fields Under Passive Restorationsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results are in agreement with the higher levels of infiltration and nutrient cycling indexes found in shrub patches in semiarid degraded steppes of Spain (Maestre and Cortina, 2004). These results can be explained by the role of shrub patches in maintaining soil stability (Bidgoli et al, 2012) and improved infiltration due to root development as found in rangeland ecosystems of Iran (Forouzeh and Sharafatmandrad, 2012).…”
Section: Landscape Function Recovery Of Fields Under Passive Restorationsupporting
confidence: 91%
“…These processes allow the landscape to function as a biogeochemical system and also to evaluate its dysfunctionality (Tongway and Hindley, 2004). Hence, the LFA methodology has been widely applied to reflect the status of critical ecosystem processes in arid lands of Australia (Ludwig et al, 2004;van der Walt et al, 2012), Iran (Ata Rezaei et al, 2006Bidgoli et al, 2012;Forouzeh and Sharafatmandrad, 2012;Siroosi et al, 2013), Mongolia (Addison et al, 2013), and Spain (Maestre and Cortina, 2004;Cortina et al, 2006;Maestre and Puche, 2009). In South American deserts, the land degradation is increasing due to intensive land use (Villagra et al, 2009), consequently emphasizing the interest in understanding ecosystem changes triggered by activities such as agriculture (Bertiller et al, 2002;Salazar et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a technique called floodwater spreading (FWS) developed by Phillips (1957) and improved by Newman (1963) and Quilty (1972), has been implemented at 36 FWS project locations in Iran since 1983 (Ghayoumian et al, 2002). The system serves as spate irrigation (Tesfai and Stroosnijder, 2001;Kowsar, 2011), artificial recharge (Hashemi et al, 2013(Hashemi et al, , 2014, soil enrichment and stabilization (Ghazavi et al, 2010), rangeland improvement (Mesbah and Kowsar, 2010;Forouzeh and Sharafatmandrad, 2012), flood mitigation (Ghayoumian et al, 2005;Kheirkhah Zarkesh, 2005), combating desertification (Kowsar, 2009), and in general, changing the outlook of deserts as potential living spaces. It is estimated that at present between 450 000 and 800 000 ha are under spate irrigation in Iran (Kowsar, 2011;Mehari et al, 2011).…”
Section: Introductionmentioning
confidence: 99%